Aortic pulse wave velocity in children with Cushing syndrome: A window into a marker of early cardiovascular disease. Issue 2 (15th January 2019) - Blain, Hailey; Sinaii, Ninet; Zeltser, Deena; Lyssikatos, Charalampos; Belyavskaya, Elena; Keil, Margaret; Bluemke, David A.; Stratakis, Constantine; Bandettini, Wiphada Patricia; Lodish, Maya
Summary: Objective: To investigate early signs of cardiovascular arterial remodelling in paediatric patients with Cushing syndrome (CS) in comparison with normative values from healthy children. Study Design: The metrics used to assess cardiac health were from thoracic aorta and carotid MRI. Scans were performed on 18 children with CS (mean: 12.5 ± 3.1 years, range: 6.0‐16.8 years, 10 female). Pulse wave velocity (PWV), aortic distensibility (AD) and carotid intima‐media thickness (cIMT), well‐validated measurements of cardiac compromise, were measured from the images and compared to normative age‐matched values where available. Results: Patients with CS had significantly higher PWV compared to age‐adjusted normal median control values (4.0 ± 0.7 m/s vs. 3.4 ± 0.2 m/s, respectively, P = 0.0115). PWV was positively correlated with midnight plasma cortisol ( r = 0.56, P = 0.02). Internal and common cIMT were negatively correlated with ascending AD ( r = −0.75, P = 0.0022, r = −0.69, P = 0.0068, respectively). Conclusion: Pulse wave velocity data indicate that paediatric patients with CS have early evidence of cardiovascular remodelling. The results suggest the opportunity for monitoring as these changes begin in childhood. Abstract : An excess of cortisol has been linked to vascular damage, leading to cardiovascular complications in patients with endogenous hypercortisolemia. The aim of this study was to assess early signs of cardiovascular remodelling associated with Cushing syndrome in paediatric patients through measurements of aortic distensibility, pulse wave velocity and carotid intima‐media thickness via MRI. This is the first study using cardiac MRI in children with Cushing syndrome.